Innate Immunity: Helping Hand for HIV Infection? - Banki, Z.; Wilflingseder, D.; Ammann, C. G.; Dierich, M. P.; Stoiber, H. (Current Medicinal Chemistry - Immunology, Endocrine & Metabolic Agents, 2004)
Similarly to other virus infections, entry of HIV into the host initiates immediate responses of the immune system. Elements of the innate immunity are activated to control HIV propagation until the induction of adaptive immunity. Innate immunity participates not only in the early phase of immune defence against HIV, but its effect can be observed continuously and concerns also modification of the adaptive immune response. In this review, we discuss the role of the innate immune system in early and late HIV pathogenesis and the escape mechanisms, which protect HIV from destruction by innate immune responses. In this regard, we will mainly focus on the interaction of HIV with various elements of innate immunity, among these the complement system, as a major humoral component. Furthermore, the involvement of cellular components of innate immunity like natural killer cells, macrophages and dendritic cells in HIV infection will be reviewed.
Keywords: HIV Infection